Association of prior criminal charges and convictions with subsequent violent and firearm-related crime: a retrospective cohort study - Julia P. Schleimer; Rachel Ross; Ali Rowhani-Rahbar (Injury Epidemiology)
Abstract Background Interpersonal violence is a pressing public health problem in the United States. Those who interact with the criminal legal system are likely to experience multiple intersecting risks that increase the probability of subsequent violence perpetration. To inform development and implementation of risk-reduction interventions within the criminal legal system or for those involved in it, there is a need for contemporary population-level estimates of violence perpetration risk among those with prior criminal charges or convictions. Methods In this state-wide retrospective cohort study of individuals in Washington state, we estimated the risk of future violent and firearm-related charges and convictions among those with misdemeanor charges or convictions for violence-related (including domestic violence), firearm-related, and substance use-related offenses from 2015 to 2019 compared to those with infractions. Subdistribution Hazard Ratios (sdHR) were used to quantify relative risk. Results Sample sized varied across comparisons, ranging from 766 people with an index firearm-related conviction to 1,280,070 with an index infraction. Relative risk of outcomes ranged from 11.73 (95% CI = 9.08–15.14) (comparing risk of subsequent violent crime conviction among those with index drug/alcohol misdemeanor convictions vs. infractions) to 155.23 (95% CI = 136.87–176.07) (comparing risk of subsequent violent crime conviction among those with index domestic violence-related misdemeanor convictions vs. infractions). Individuals with domestic violence-related misdemeanor convictions had over 30 times the risk of subsequent firearm-related charges and convictions compared to those with infractions. Conclusions Findings from this state-wide study inform opportunities to reduce risk for subsequent violence and firearm-related harm, for example through tailored intervention, investment in healing-centered deflection strategies, and improved implementation of domestic violence firearm prohibitions.